Chronic effects of flywheel training on physical capacities in soccer players: a systematic review. Issue 3 (4th May 2023) - Allen, William J.C.; De Keijzer, Kevin L.; Raya-González, Javier; Castillo, Daniel; Coratella, Giuseppe; Beato, Marco
ABSTRACT: The aims of the current systematic review were to evaluate the current literature surrounding the chronic effect of flywheel training on the physical capacities of soccer players, and to identify areas for future research to establish guidelines for its use. Studies were identified following a search of electronic databases (PubMed and SPORTDiscus) in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA). Eleven studies met the inclusion criteria and were included. The methodological quality of the included studies ranged between 10 and 18 with an average score of 15 points using the PEDro scale. The training duration ranged from 6 weeks to 27 weeks, with volume ranging from 1 to 6 sets and 6 to 10 repetitions, and frequency from 1 to 2 times a week. This systematic review reported that a diverse range of flywheel training interventions can effectively improve strength, power, jump, and changes of direction in male soccer players of varying levels. Flywheel training interventions improve the physical capacities of soccer players of varying levels. Nonetheless, the current literature suggests contrasting evidence regarding flywheel training induced changes in sprint speed and acceleration capacity of soccer players.